INTERPERSONAL LANGUAGE IN STUDENT INTERACTION DISCOURSE IN THE CLASS OF SMP NEGERI 5 MANUJU (FUNCTIONAL SYSTEMIC LINGUISTICS STUDY) - Irmawati irma; Munirah; Siti Suwadah Rimang (PT. Jurnal Center Indonesia Publisher, 2026)
This study analyzes the interpersonal language actions used by students in class interactions at SMP Negeri 5 Manuju with the Functional Systemic Linguistics (LSF) approach. This approach emphasizes the role of language as a tool to build social meaning and facilitate interaction in the context of learning. The purpose of the research is to understand how students use language to communicate, coordinate, and negotiate meaning in learning activities. The research method used is qualitative descriptive with data collection through direct observation of classroom interactions, in-depth interviews with teachers and students, and documentation in the form of recordings and field notes. Data analysis is carried out interactively through the stages of collection, reduction, presentation, and extraction of meaning from interpersonal utterances that appear in learning. The results showed that students' interpersonal language actions were realized through three types of mood clauses: interrogative, used to ask questions and ask for clarification; declarative, used to convey an opinion or information; and imperative, used to direct group work with mitigation to maintain social harmony. The function of this language act is not only to convey information, but also to build social relationships, organize group collaboration, and provide subtle approval or support. These findings provide an overview of how language plays a role in shaping communicative and collaborative interactions in the classroom.